PTU-104 Maximising access to hcv treatment – the sunshine coast experience. (17th June 2017) - White, L; Kay, B; Higgins, S; Kaye, S; Sloss, A; Weston, N; O'Beirne, J; Mitchell, JD
Abstract : Introduction: Hepatitis C virus (HCV) affects approximately 230000 Australians and leads to cirrhosis, progressive liver failure and hepatocellular carcinoma (HCC). The introduction of directly-acting antiviral (DAA) therapies has revolutionised management due to improved tolerability and efficacy. Unlike other health systems funding for unrestricted access to DAA for all HCV infected Australians was introduced in 2016 with the aim of eradicating HCV. However, current models of HCV treatment that are hospital based represent a barrier to treatment for many Australians due to remoteness from treating centres. To improve access to treatment the hepatology service at the Sunshine Coast Hospital and Health Service (catchment area 11 000 km 2, population 400, 000) has explored new models of care for DAA therapy such as basing treatment in local primary care. Method: From March 1 st, 2016 patients were assessed for suitability of and prescribed DAA for the treatment of HCV. Patients were initially assessed by a specialist Hepatology service and DAA were prescribed either by Hepatologists at treating centre or primary care physicians after a treatment recommendation. Follow up was by hepatologists and clinical nurses within a hospital setting or physicians in primary care. The decision regarding treatment and follow up was assessed on a case by case basis taking into consideration fibrosis stage, comorbidities and geographical proximity to the main hospital service. The mean age of patients was 51y (18-69y), 67% were male. Genotype 1 and 3 were most common (G1a 41%, G1b 11.4%, G2 6.5% and G3 40.9%). The majority of patients were non cirrhotic (F0 20%, F1 24%, F2 17%, F3 9%, F4 30%) and treatment naïve (74% vs 26%). Therapies prescribed were Sofosbuvir/Ledipasvir (50%), followed by Sofosbuvir/Daclatasvir (33%), Sofosbuvir/Daclatasvir/Ribavirin (10%), Sofosbuvir/Ribavirin (5%), ViekiraPak (1%) and Elbasvir/Grazoprevir (1%) Results: Until January 2017, 508 patients have been initiated on DAA therapy. 416 (84%) had hospital based treatment and 80 (16%) had treatment initiated and monitored in primary care. SVR at 12 weeks (SVR12) is available for 222 patients. SVR12 has been achieved in 96.7% to date with 7 people failing treatment. SVR by fibrosis stage ranged from 93%–100% (F0 100%, F1 98%, F2 93%, F3 94%, F4 98%). SVR12 in the primary care cohort to date is 93% (n=27). p=0.224 compared to hospital based treatment (97%) Conclusion: The use of primary care for initiation and monitoring of DAA offers the potential to maximise access and reduce costs associated with HCV treatment whilst maintaining high SVR rates. Continued prescription and management in this model of care will allow for ongoing successful eradication of Hepatitis C virus in Australia Disclosure of Interest: None Declared